Economic Valuation of Lapin Beach Tourism in Rupat Utara Sub-District, Bengkalis Regency - Siregar, Cici Y.P.; Warningsih, Trisla; Darwis, Darwis (Faculty of Fisheries and Marine, Universitas Riau, 2024)
Bengkalis is one of the districts in Riau Province with a strategic position in developing coastal tourism because it deals directly with international shipping. Lapin Beach is a tourist attraction in the Rupat Utara District, Bengkalis Regency. This research was conducted at Lapin Beach, Tanjung Punak Village, in March 2023. This research aimed to determine the factors that influence the number of visits to Lapin Beach and the economic value of Lapin Beach. The method used in this research is a survey method to provide a detailed description of the background, characteristics, and typical characteristics of a general object or event. Data analysis uses multiple linear regression methods, and travel cost analysis uses the travel cost method approach. The research results show that the factors that influence the number of tourist visits are influenced by travel costs, distance, income, education, and length of time knowing about the existence of the beach, so the consumer surplus value obtained is IDR 251,917,538.8. The total economic value of Lapin Beach is IDR 118,356,787,199.48.